Pengaturan BPHTB Terutang dalam Penyelenggaraan Program Pendaftaran Tanah Sistematik Lengkap (PTSL) - Deriangga Arrahmad Rahadiansyah; Habib Adjie (Universitas 45 Surabaya, 2024)
This paper aims to review the legal certainty of the regulation outstanding land and building rights “perolehan hak atas tanah dan bangunan” (BPHTB) in the implementation of complete systematic land registration “pendaftaran tanah sistematik lengkap” (PTSL). This study uses normative research with legal approach that related regulation land registration. The problems in this study are in the presence the norm conflicts between article 33 point 1 and 2 “ Peraturan Menteri Agraria dan Tata Ruang Nomor 6 Tahun 2018” about complete systematic land registration that holders of land rights from PTSL have the obligation to pay BPHTB that contrary to article 3 “Undang undang Nomor 20 tahun 2000” about the Duty to Obtain Land and Building Rights which states that government programs for development are not objects of BPHTB.